2015
DOI: 10.1177/1541931215591327
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Robot Form on Trust

Abstract: Assistive robotics is a rapidly progressing field of study that contains facets yet to be fully understood. Here we look at the effect of robot form on user’s level of trust placed on the robot. Form-based trust was evaluated in this study by comparing participant trust ratings based on four robot designs: Lego Mindstorm, Keepon, Sphero and Ozzy. The first view of the robot and the interactions with the robots were examined with pre and post measurements of trust. Sphero and Lego received consistently higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ref. [41] conducted a series of experiments on robots from different domains to explore the impact of robot attributes such as form and functions in the human-robot trust relationship. Ref.…”
Section: Usersmentioning
confidence: 99%
“…Ref. [41] conducted a series of experiments on robots from different domains to explore the impact of robot attributes such as form and functions in the human-robot trust relationship. Ref.…”
Section: Usersmentioning
confidence: 99%
“…The morphology of social robots is often classified into anthropomorphic (i.e., human-like), zoomorphic (i.e., animal-like), caricatured (i.e., cartoon-like), and functional (i.e., form follows function) [2]. Different morphologies can elicit differences in how users perceive and interact with robots, as research on adult robot-users has shown (e.g., [3][4][5]). Focusing on child-robot interaction (CRI) more specifically, research has shown that robot morphology affects children's role attribution to, and satisfaction with, robots [6]; their perception of a robot's emotions [7], feelings, personality, and cognitive abilities [8]; and their attitudes towards robots [9].…”
Section: Introductionmentioning
confidence: 99%